2008
DOI: 10.1249/mss.0b013e3181632d2d
|View full text |Cite
|
Sign up to set email alerts
|

HDL Atheroprotection by Aerobic Exercise Training in Type 2 Diabetes Mellitus

Abstract: Our results show that aerobic exercise training in diabetes mellitus improves the HDL efficiency against LDL oxidation and favors HDL maturation. These findings were independent of changes in insulin resistance and of the rise of plasma HDL cholesterol concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 43 publications
1
13
1
4
Order By: Relevance
“…As shown in ESM Table 1, across 20 interventions of aerobic exercise training, [8,9,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] the mean exercise frequency was three sessions per week, mean session duration was 48 min (not including warm-up and cool down), and mean exercise intensity was 74% of the HR max . In six trials (33%), exercise intensity was transformed from submaximal rates of V : O 2peak to the corresponding percentages of HR max .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in ESM Table 1, across 20 interventions of aerobic exercise training, [8,9,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] the mean exercise frequency was three sessions per week, mean session duration was 48 min (not including warm-up and cool down), and mean exercise intensity was 74% of the HR max . In six trials (33%), exercise intensity was transformed from submaximal rates of V : O 2peak to the corresponding percentages of HR max .…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence supports the recommendation of regular physical activity for the prevention and treatment of diabetes and other chronic diseases that present a constant proinflammatory status [19]. The practice of regular physical activity is known to bring health benefits such as increased insulin sensitivity, glycaemic control, decrease of body weight and percentage of body fat, lower blood pressure and reduction of overall risk of vascular disease [6,8,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Potentially more important than HDL-C levels, however, is how exercise may improve HDL function. For example, exercise has been reported to increasing the cholesterol efflux capacity of HDL isolated from metabolic syndrome patients (Casella-Filho et al, 2011), although this was not observed in a previous study (Ribeiro et al, 2008). In another study, exercise training in chronic heart failure (CHF) patients increased the ability of their HDL to promote NO production and flow-mediated dilatation (Adams et al, 2013).…”
Section: Hdl and Inflammationmentioning
confidence: 92%